KEPUASAN PELANGGAN DITINJAU DARI KUALITAS PELAYANAN, KEBERAGAMAN PRODUK, DAN STORE ATMOSPHERE PADA ANAK PANAH KOPI PLUS DI SOLO BARU - Elen Sasa Belia Ornelia; Siti Maryam; Fithri Setya Marwati (JURNAL ILMIAH EDUNOMIKA, 2023)
This study aimed to ascertain and analyse the impact of service quality, product variety, and store atmosphere on customer satisfaction at Anak Panah Kopi Plus Solo Baru. This investigation was carried out at Anak Panah Kopi Plus Solo Baru. This study employs a quantitative approach. This investigation required three months to conclude. Infinite customers of Anak Panah Kopi in Solo Baru constituted the population of this investigation. This survey's sample consisted of 100 respondents. This research employs a non-probabilistic sampling strategy with methods of purposive sampling. The results indicated that service quality, product variety, and store atmosphere have a positive and significant effect on the consumers of Anak Panah Kopi Plus in Solo Baru. According to the results of the test for the coefficient of determination, service quality, product diversity, and store atmosphere influence customer satisfaction at Anak Panah Kopi Plus in Solo Baru by a model variable of 49.4%, while the remaining model variable of 50.6% is influenced by other factors not considered in this study. Keywords : Service Quality, Product Diversity, Store Atmosphere, Customer Satisfaction